A Methods Engineering Study on Lite Metals Manufacturing - Cortez, Catherine; Jasa, Jose Leonardo; Lee, Ma. Glaiza; Lim, Paul Andrews (College of Engineering, 2006)
Lite Metals Manufacturing is a single proprietorship company that produces Aluminum Wheels for four wheel vehicles and tricycles. It is also an importer and a distributor of the said products. The present system of the company was first documented by the group through direct observation and interviews with the owner and the workers. It was also through these that the group was able to determine the actual problems being encountered by the company in its manufacturing processes. A Stream Diagnostic Chart was used to determine the root causes of all the problems or failures encountered by the company. The three root causes were the inefficiency in the plant layout, the poor working conditions, and the highly manual tools and semi-automatic machines used in the company. Alternatives addressing the issues that were under the three root causes were generated. The 'must' objectives were listed down to determine if the alternatives were valid and feasible. Although the insufficiency of forms was not one of the root causes, the group decided to address this problem so that the company could have quantitative data for monitoring its current processes and for future studies. The final recommendations were determined by checking which alternative satisfies the 'want' objective the most. The chosen plant layout involved moving major machines but had the storage area near the gate, the areas of subsequent processes adjacent to each other, and the related processes grouped together. Furthermore, a new setup for the seated operations, added light sources and ventilation sources, and appropriate safety gears were also recommended to improve the working conditions of the employees. A cost-benefit analysis on the acquisition of new machines was also suggested to address the problems in the inconsistency of manual labor. Finally, three new forms were recommended to monitor and document the processes in the company. A 12 month implementation plan was also provided which can be altered by the management as it sees fit in order to best suit the needs of the company.